TAKING INTERDEPENDENCIES SERIOUSLY: THE CASE OF MOZILLA’S ENTANGLEMENTS WITH JOURNALISM - Baack, Stefan; Conill, Raul Ferrer; Cheruiyot, David (AoIR Selected Papers of Internet Research, 2021)
Despite the complex interdependencies in today’s digital news ecology, it is still common to study digital journalism primarily by looking at how ‘non-journalists’ are influencing journalists from ‘outside’ the field of professional journalism. When it comes to how digital journalism is shaping non-journalists, we mostly find audience research or research on the effects of journalistic reporting. We argue that understanding journalism’s role in society today requires us to more broadly ask how imaginaries about journalism influence all kinds of actors that make up our digital public. In this paper, we therefore discuss how imaginaries about journalism shape the practices and identity of Mozilla, an organization best known for the development of the Firefox web browser. Mozilla currently explores collaborations with, or support of journalism, and we argue that this exploration is shaped by imaginaries about journalism. Using a Mozilla project as an example that seeks to support alternatives to advertising as the dominant way to finance journalistic content online, we show how Mozilla is trying to support its own mission by supporting organizations whose practices and values are considered compatible with this mission. We argue that Mozilla is not aiming to support ‘journalism’ as such, but a particular and rather traditional idea of fact-oriented journalism that facilitates political deliberation. Our findings suggest that studying how particular imaginaries about digital journalism influence non-journalists can help illuminate journalism’s role in today's digital news ecology beyond its ‘democratic function’ and contribute to a more nuanced understanding of the digital transformation as a whole.